MANAGEMENT OF VILLAGE FUND ALLOCATION IN DEVELOPMENT IMPLEMENTATION IN OROBUA MARAMPAN VILLAGE, SESENAPADANG DISTRICT, MAMASA REGENCY - Iskandar, Andi Arifuddin; Arniati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study was to determine the effectiveness of village fund allocation in the implementation of development in Marampan Orobua Village, Sesenapadang District, Mamasa Regency. This study used a descriptive survey method. The data obtained in this study are primary data through filling out a questionnaire. The test used is the validity test, reliability test, and effectiveness test. The results showed that the Fund Allocation Management in the Implementation of Development in Marampan Orobua Village, Sesenapadang District, Mamasa Regency was effective with a percentage of 100%. The allocation of village funds seen in the context of planning, implementation and supervision for the community has been carried out well but has not been fully in accordance with the expectations of rural communities who want an increase in the budget and implementation of village development.